2015
DOI: 10.4172/2155-9600.1000348
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Impact of Dietary Calcium Sources on Serum Calcium and Bone Reformation Using an Ovariectomized Sprague-Dawley Rat Model

Abstract: Osteoporosis is a multifactorial skeletal disease that is characterized by compromised bone strength predisposing a person to an increased risk of fracture. This ovariectomized (OVX) Sprague-Dawley rat model study measured the changes in serum calcium, as well as femur dimensions and mineral density, when consuming calcium carbonate, calcium gluconate and salmon bone calcium. Our results show that salmon bone calcium and to a lesser extent calcium gluconate showed a statistically significant increase in femur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies have shown that the intake of Collagen has a positive effect of increasing BMD in several in-vivo bone growth models [10]. CalGo™ has also shown an osteoinductive effect by increasing osteoblast activity in-vitro [11] and in-vivo [12].…”
Section: Calcium Supplementation Has Been a Cornerstone In These Atte...mentioning
confidence: 99%
“…Studies have shown that the intake of Collagen has a positive effect of increasing BMD in several in-vivo bone growth models [10]. CalGo™ has also shown an osteoinductive effect by increasing osteoblast activity in-vitro [11] and in-vivo [12].…”
Section: Calcium Supplementation Has Been a Cornerstone In These Atte...mentioning
confidence: 99%